Neonatal Jaundice: Its Determinants Among Neonates Admitted to Neonatal Intensive Care Units of Tigray Region General Hospitals, Northern Ethiopia - Berhe Mengesha Kiros MPH; Girmatsion Fisseha PhD; Assefa Ayalew Gebreslassie MPH; Zenawi Hagos Gufue MPH; Haftamu Ebuy MPH; Molla Teferi Belew MPH; Getachew Zinabu Reda MSC; Hayat Maeruf Mohammed MSC (SAGE Publishing, 2023)
Background. Despite the significant public health impact of neonatal jaundice on neonatal survival, local epidemiologic data are scarce. Methods. A multi-centered, unmatched case-control study was conducted among 180 consecutively admitted neonates (60 cases and 120 controls). The independent determinants of newborn jaundice were determined using a multivariable binary logistic regression model, and a P -value of <0.05 was used to indicate statistical significance. Results. Maternal medical complications during the index pregnancy (AOR = 2.45; 95% CI 1.01-5.97), rural residence (AOR = 3.1; 95% CI 1.02-9.42), being a low birthweight neonate (AOR = 3.42; 95% CI 1.12-10.41), neonatal B blood group (AOR = 10.19; 95% CI 2.89-35.9), neonatal O blood group (AOR = 2.99; 95% CI 1.04-8.59), and a longer duration of hospital stay (AOR = 9.83; 95% CI 3.11-31.02) were the independent determinants of neonatal jaundice. Conclusions. Early assessment of high-risk neonates might reduce the long-term neurodevelopmental consequences.